Corruption and Development - Gray, Cheryl W.; Kaufman, Daniel (World Bank, Washington, DC, 2012)
This public sector note analyzes the issue of the growing recognition and discussion of corruption, and in turn facilitates addressing its costs and causes. Through the examination of corruption causes in developing countries and transition economies, it is suggested that prevailing bribery, hence corruption, imposes a significant tax on foreign direct investment in all regions. Thus the cost of capital for firms increases greatly. The note focuses on the creation of a political will and constructive pressure, as well as assistance from international organizations and donors in fighting corruption, by supporting government reforms in economic policies, institutions, and the pursuit of a healthy civil society.